2022
DOI: 10.3171/2021.12.jns212193
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temporal muscle thickness on the outcome of radiosurgically treated patients with brain metastases from non–small cell lung cancer

Abstract: OBJECTIVE The purpose of this study was to assess the impact of temporal muscle thickness (TMT), a surrogate marker for sarcopenia, in radiosurgically treated patients with brain metastases (BMs) from non–small cell lung cancer (NSCLC). METHODS For 566 patients with BMs from NSCLC in the period between June 2012 and December 2019, TMT values were retrospectively measured on the planning brain magnetic resonance imaging (MRI) studies that had been obtained before their first Gamma Knife radiosurgery treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
(70 reference statements)
0
12
0
1
Order By: Relevance
“…Current systematic review suggests that sarcopenia negatively affects prognostic outcomes of cancer patients in terms of survival, physical activity, length of hospital stay and other complications [16][17][18][19][20][21][22]. However, we found that current studies were limited to specific primary tumors or site-specific metastatic cancers [23][24][25]. While sarcopenia as a systemic disease, we hypothesize that it is closely associated with the prognosis of multiple metastatic cancers.…”
Section: Introductionmentioning
confidence: 73%
“…Current systematic review suggests that sarcopenia negatively affects prognostic outcomes of cancer patients in terms of survival, physical activity, length of hospital stay and other complications [16][17][18][19][20][21][22]. However, we found that current studies were limited to specific primary tumors or site-specific metastatic cancers [23][24][25]. While sarcopenia as a systemic disease, we hypothesize that it is closely associated with the prognosis of multiple metastatic cancers.…”
Section: Introductionmentioning
confidence: 73%
“…Current systematic review suggests that sarcopenia negatively affects prognostic outcomes of cancer patients in terms of survival, physical activity, length of hospital stay and other complications (16)(17)(18)(19)(20)(21)(22). However, we found that current studies were limited to speci c primary tumors or site-speci c metastatic cancers (23)(24)(25). While sarcopenia as a systemic disease, we hypothesize that it is closely associated with the prognosis of multiple metastatic cancers.…”
Section: Introductionmentioning
confidence: 79%
“…Most of the studies were conducted in Austria (6 studies). 4 , 8 , 24 , 25 , 26 , 27 There were two studies from Turkey, 28 , 29 two from USA, 30 , 31 two from Germany, 32 , 33 two from Italy, 34 , 35 one from South Korea, 36 one from the Netherlands 37 and one from China. 38 Our review includes 17 retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%